Uwagi o przebiegu XVI-wiecznych procesów normalizacyjnych na przykładzie oboczności albo // abo - Michalska-Górecka, Paulina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The aim of the article is to demonstrate the rivalries stemming from the Old-Polish variant forms/ albo and abo in the 16th-century printed material from Cracow, having the strongest influence upon the forming literary Polish language. The article tries to answer the question how a certain linguistic custom was established, not being a norm yet. For comparison, the process has also been shown in the prints from the northern borderland of Poland and Great Poland, the regions which at that time did not have such a significant influence on the literary language as the prints from Cracow, but also produced more books than other regions. The listing of data from three regions makes it possible to show the differences in the formation of the norm between the centre of cultural life of the Republic of Poland (Cracow) and its peripheral regions – the eastern and the western.